Autophagy modulation in MEK inhibitor‐resistant melanoma. (1st February 2019) - Verykiou, S.; Alexander, M.; Edwards, N.; Plummer, R.; Chaudhry, B.; Lovat, P.E.; Hill, D.S.
Summary: Malignant melanoma tumour cells often carry mutations in the BRAF protein, which activates a second protein called MEK to fuel tumour growth. Using drugs that block the mutant form of BRAF and MEK, we can specifically target and kill most of these tumour cells, but a subset of tumour cells often become resistant to BRAF and MEK inhibiting drugs, and cause the tumour to regrow. The aim of this study was to determine how changes in a protein called CD271, which has previously been shown to increase tumour growth and aggressiveness, contributes to the resistance of BRAF mutant melanoma cells to the MEK inhibiting drug, trametinib. Furthermore, we have previously shown that a cell survival process within tumour cells called autophagy is increased in BRAF mutant melanoma cells, so we also aimed to determine the contribution of autophagy to the resistance of BRAF mutant melanoma cells to trametinib. We show that CD271 and autophagy are increased in advanced malignant melanoma tumours compared to normal moles, and that treatment of melanoma cells in the laboratory with trametinib results in the emergence of a subset of melanoma cells with increased CD271 and autophagy. However, specific inhibition of CD271 reduced the number of resistant melanoma cells following trametinib treatment, while either blocking or activating autophagy resulted in death of trametinib‐resistant melanoma cells. We also show that combined treatment with drugs that specifically block both MEK and autophagy reduced the invasion of trametinib‐resistant melanoma cells in embryonic zebrafish up to 5 days old. Our results show that embryonic zebrafish at an early stage of development may replace mice as a more ethical alternative animal model for the study of cancer metastasis (spreading) and drug response, and highlight an important new way to prevent drug‐resistance by blocking autophagy in patients with BRAF mutant melanoma cells.